2021
DOI: 10.1021/acsomega.1c00289
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Quality Assessment of Kaixin Powder by HPLC–DAD Quantification and HPLC–QTOF-MS/MS Confirmation

Abstract: Kaixin Powder (KXP) is a classic formula for treating morbid forgetfulness in ancient China. To guarantee the efficacy and safety of KXP, a simple and accurate HPLC–DAD method has been established and validated for the quantitative analysis of seven bioactive compounds in KXP. Dehydrotumulosic acid (DTU) and dehydrotrametenolic acid (DTR) were quantified in KXP for the first time. Good chromatographic separation was conducted on a Kromasil 100-5 C 18 column (250 mm × 4.6 mm, 5 μm) by gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…They have found several bioactive compounds: ginsenosides, 3,6′disinapoyl sucrose, α/β-asarone, and pachymic acid for Ginseng Radix et Rhizoma, Polygalae Radix, Acori Tatarinowii Rhizoma, and Poria in KXP based on LC-MS, respectively (Zhu et al, 2010). Apart from these five compounds, Wang et al (2021), have firstly found two novel bioactive compounds of KXP (dehydrotrametenolic and dehydrotumulosic acids) from KXP using HPLC-DAD and HPLC-QTOF-MS/MS. These efforts have also resulted in the widespread use of chromatographic methods for TCM formula quality assessment (Liu et al, 2016b;Fan et al, 2021;Zeng et al, 2021).…”
Section: The Methods For Chemical Ingredient Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…They have found several bioactive compounds: ginsenosides, 3,6′disinapoyl sucrose, α/β-asarone, and pachymic acid for Ginseng Radix et Rhizoma, Polygalae Radix, Acori Tatarinowii Rhizoma, and Poria in KXP based on LC-MS, respectively (Zhu et al, 2010). Apart from these five compounds, Wang et al (2021), have firstly found two novel bioactive compounds of KXP (dehydrotrametenolic and dehydrotumulosic acids) from KXP using HPLC-DAD and HPLC-QTOF-MS/MS. These efforts have also resulted in the widespread use of chromatographic methods for TCM formula quality assessment (Liu et al, 2016b;Fan et al, 2021;Zeng et al, 2021).…”
Section: The Methods For Chemical Ingredient Analysismentioning
confidence: 99%
“…Network pharmacology analysis is presented to clarify which compounds of TCM formula exert effects in treating diseases and which targets could be exploited for drug design (Boezio et al, 2017;Wu et al, 2018;Zhang et al, 2019b), which has developed into a powerful method for leveraging the "ingredients-compounds-proteins/genesdiseases" network for TCM research (Zhang et al, 2019b;Yang et al, 2022). Multi-omics such as transcriptomics, genomics, epigenomics, and proteomics could be used to determine the ingredients, proteins, and/or genes of TCM formulas, whereas electrochemical method, HPLC, real-time qPCR, and other quantified methods can be used to determine and quantify the content of bioactive compounds (Wolfender et al, 2003;Zhu et al, 2010;Wang et al, 2021). While network pharmacology analysis could facilitate the integration of ingredients, bioactive compounds, and proteins/ genes into a network, providing an effective resolution for exploring the TCM-disease interaction (Zhang et al, 2019b).…”
Section: Multi-omics Approaches For Tcm Network Analysis Researchmentioning
confidence: 99%
“…The basic feature of TCM is that it consists in the form of preparation and formulation by the guidance of compatibility rules, different herbs are usually orchestrated to form a multi-herbs combination. A classical prescription generally contains primary (called “Jun” or “Emperor”) and adjuvant herbs (called “Chen, Zuo, and Shi”) according to the therapeutic characteristics of TCM, and the latter function as “Assistant”, “Vassal” and “Delivery servant” which are generally worked as assistants to increase efficiency, enhance the synergistic effect or to facilitate the delivery of the emperor medicine ( Wang et al, 2021a ). In the TCM system, the incorporation of a “Delivery servant” into classical prescription is an important compatibility mechanism to support the transportation from the effective constituents to the target organ in treating diseases ( Wei et al, 2018 ).…”
Section: Pharmacokinetic Studiesmentioning
confidence: 99%